Avaliação da eficiência de vacinas contra Clostridium novyi tipo B. - Ricardo Aurelio Pinto Nascimento (2003)
The antibody response to the Clostridium novyi type B alfa toxin component of thirteen commercial vaccines (T1 to T13) and a standard toxoid was evaluated by the serum neutralization test with rabbit and and bovine será and by direct challenge of vaccinated guinea pigs. T1, T10 and the standard toxoid induced titles of C. novyi type B alfa antitoxin in rabbit superior to the recommended minumum title of 3,5 IU/mL, namely of 8 IU/mL, 12 IU/mL and 15 IU/mL, respectively. T2 and T5 induced titles of 2 IU/mL and 3 IU/mL, respectively. These, plus T1 and T10, were also the only vaccines which produced detectable guinea pigs at the challenge. The same group, plus T11, were able to protect all the vaccinated guinea pigs at the challenge. The majority of the C. novyi type B vaccines in commerce in Brazil were unable to induce the minimum antibody response recommended for approval of the product